Nephrology reviews (PAGEPress, 2009)
Abstracts and comments on recent articles in basic and clinical research in nephrology. Articles appeared mostly in English-language journals. Arranged under 8 sections, e.g., Renal physiology, Glomular diseases, and Hypertension. Each entry gives bibliographical information, institution of authors, abstract, and signed comments. No index.